The Protective Effects of miR-21-Mediated Fibroblast Growth Factor 1 in Rats with Coronary Heart Disease. (1st December 2021) - Zhang, Bin; Liu, Hongguang; Yang, Guoping; Wang, Yongmei; Wang, Yan
Abstract : Aim . The study is to verify the protective effects of miR-21-mediated fibroblast growth factor 1 (FGF1) against myocardial ischemia in rats with coronary heart disease. Materials and Methods . Sprague-Dawley (SD) rat models of myocardial ischemia/reperfusion (MI/R) injury were constructed, and the expression of miR-21 and FGF1 in them was interfered through ischemic postconditioning. The protective effects of miR-21-mediated FGF1 on myocardium of the model rats were analyzed, and the targeted regulatory relationship between miR-21 and FGF1 was verified through myocardial cell experiments to find the mechanism of miR-21. Results . MiR-21 and FGF1 with increased expression could protect the cardiac function of model rats and improve their diastolic blood pressure (DBP), systolic blood pressure (SBP), heart rate (HR), coronary flow (CF), bax, and bcl-2 levels, but it would also cause further increase of vascular endothelial growth factor (VEGF) and decreased infarct size (INF). In addition, intervention through both miR-21 mimics and recombinant human FGF1 could highlight the above changes. Pearson correlation analysis revealed that the expression of miR-21 was positively correlated with that of FGF1, and both miR-21 and FGF1 were significantly and linearly correlated with DBP, SBP, HR, CF, INF, bax, and bcl-2, but they were not significantly correlated with the VEGF level. The myocardial cell experiment results revealed that upregulation of miR-21 or FGF1 could alleviate apoptosis caused by hypoxia/reoxygenation of myocardial cells, and inhibition of the FGF1 expression could hinder the effect of miR-21 against apoptosis of myocardial cells. Dual luciferase reporter assay revealed that transfection of miR-21-mimics could effectively raise the fluorescence intensity of pmirGLO-FGF1-3 ′ UTR Wt but had no significant effect on that of pmirGLO-FGF1-3 ′ UTR Mut. Conclusion . MiR-21 can specifically mediate the expression of FGF1 to relieve MI/R injury, protect the cardiac function, and resist apoptosis.